The Followers of the Stars: on the Early Sources and Historical Development of Indian Astrology - Beinorius, Audrius (Acta Orientalia Vilnensia, 2003)
This article sets itself a goal to explore the early historical development of the traditional astrological sciences (jyotiṣaśāstra, jyotiṣavidyā) in India, tracing its relationship to the astrology developed in Mesopotamia and in the Hellenistic period by the Greeks, as well as discussing some of its amplifications in South Asia, and the direct intercourse between India and the Arabs. Some attention is paid to the transformation and re-interpretation of foreign astral and divinatory sciences in India. The primarily sources of the present study are the early Sanskrit texts (mainly those of Sphujidhvaja’s and Varāhamihira’s, and the study itself is grounded on the critical analysis of contemporary discussions carried on by D. Pingree, O. Neugebauer, P. V. Kane, A. M. Shastri, and others scholars in the field.